2022
DOI: 10.1152/ajplung.00428.2021
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical JAK1/STAT3 interactions with TGF-β modulate myofibroblast transdifferentiation and fibrosis

Abstract: Idiopathic pulmonary fibrosis is a progressive lung disease with limited survival. The specific roles of Janus Kinases - tyrosine kinases that transduce cytokine-mediated signals - in lung fibrosis are not well defined. In this study, the interactions between JAK1/STAT3 signaling and TGF-β induced fibroblast responses were investigated using both pharmacological and siRNA approaches in human normal and IPF-derived lung fibroblasts. We found that JAK1 directly interacts with the TGF-β receptor I (TβRI), and sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Studies have shown that TGF‐β stimulates local and bone fibroblasts to differentiate into myofibroblasts, allowing an increase in the number of myofibroblasts in HS; actin filaments in myofibroblasts contribute to wound contraction and the production of tension on the wound 45 . According to previous studies, TGF‐β can activate STAT3 or mutually regulate with STAT3 in various manners to promote fibrosis of organs and tissues 46–48 . Western blot analysis in this study showed that both AC and si‐STAT3 could significantly downregulate the TGF‐β1 protein level in HSFs, indicating a negative regulatory effect of AC on the expression and signaling of TGF‐β1 in HSFs.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Studies have shown that TGF‐β stimulates local and bone fibroblasts to differentiate into myofibroblasts, allowing an increase in the number of myofibroblasts in HS; actin filaments in myofibroblasts contribute to wound contraction and the production of tension on the wound 45 . According to previous studies, TGF‐β can activate STAT3 or mutually regulate with STAT3 in various manners to promote fibrosis of organs and tissues 46–48 . Western blot analysis in this study showed that both AC and si‐STAT3 could significantly downregulate the TGF‐β1 protein level in HSFs, indicating a negative regulatory effect of AC on the expression and signaling of TGF‐β1 in HSFs.…”
Section: Discussionsupporting
confidence: 59%
“…or mutually regulate with STAT3 in various manners to promote fibrosis of organs and tissues. [46][47][48] Western blot analysis in this study showed that both AC and si-STAT3 could significantly downregulate the TGF-β1 protein level in HSFs, indicating a negative regulatory effect of AC on the expression and signaling of TGF-β1 in HSFs.…”
Section: Discussionmentioning
confidence: 60%
“…JAK, a tyrosine kinase, facilitates STAT signaling, with JAK1 and STAT3 serving as pivotal proteins in the JAK/STAT3 pathway [25]. JAK/STAT3 signaling is known to play a crucial role in tumor cell invasion, angiogenesis, and proliferation [26].…”
Section: Discussionmentioning
confidence: 99%
“…In support of this finding, several studies have demonstrated that independent of the Smad pathway, TGFβ1 can induce Stat3 phosphorylation likely through the activation of JAK1, an upstream kinase of Stat3 in other cell types. 36 , 37 More specifically, after TGFβ1 treatment, phosphorylated TβRI directly binds to and activates JAK1. Activated JAK1 can further phosphorylate Stat3.…”
Section: Discussionmentioning
confidence: 99%
“…Activated JAK1 can further phosphorylate Stat3. 37 , 38 Further evidence showed TGFβ-Jak1-Stat3 pathway is required to cooperate with Smad3 for mediating TGFβ-induced fibrotic response in hepatic stellate cells. 38 Mechanistically, phosphorylated Stat3 forms a complex with Smad3 and promotes its nuclear localization thereby enhancing fibrotic-related gene transcription.…”
Section: Discussionmentioning
confidence: 99%